The role of the parties to the international investment contract in restoring its financial balance - Boutabala, Mammar (Journal of Human Sciences, 2023)
This study aims to show the role played by the various agreement tools available to the parties to international investment contracts with extended terms in restoring their lost financial balance because they are implemented over successive periods, which in most cases exposes them to exceptional and unexpected circumstances that implement the commitment possible, but it is characterized by difficulty and hardship, in implementation, which tells the debtor to a heavy loss, which necessitates returning the burdensome obligation to a reasonable extent to preserve the sustainability and stability of contractual ties and to establish the principle of contractual justice that dominates international cross-border trade transactions.